A critical analysis of the adventure tourism higher education landscape in South Africa - Hermann, U. P. (South African Journal of Higher Education, 2026)
The adventure tourism sector continues to grow in both developed and developing countries. With this growth, there also exists an increased demand for qualified and highly trained employees that are ready for the real world of work. Further education and higher education institutions (HEIs) serve as platforms for the development of this much needed human resource. Specialised curricula, form the basis on which this human capacity is developed. However, not much is known about the landscape of adventure tourism higher education offerings in South Africa, in particular. This article seeks to address this shortcoming by critically analysing the adventure tourism higher education landscape in South Africa. Results are presented and recommendations are made to further the academic discourse in adventure tourism curriculum development.